2012
DOI: 10.3727/096368911x627552
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cells Improve Cardiac Function in Doxorubicin-Induced Cardiomyopathy Mediated through Multiple Mechanisms

Abstract: Doxorubicin (DOX) is an effective antineoplastic agent used for the treatment of a variety of cancers. Unfortunately, its use is limited as this drug induces cardiotoxicity and heart failure as a side effect. There is no report which describes whether transplanted embryonic stem (ES) cells or their conditioned medium (CM) in DOX induced cardiomyopathy (DIC) can repair and regenerate myocardium. Therefore, we transplanted ES cells or CM in DIC to examine apoptosis, fibrosis, cytoplasmic vacuolization and myofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
83
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(97 citation statements)
references
References 38 publications
14
83
0
Order By: Relevance
“…These beneficial effects have been attributed to decreased collagen deposition, enhanced myocardial regeneration, and possible paracrine factors released from ESCs such as the anti-apoptotic proteins cystatin C, osteopontin, and clusterin, and the anti-fibrotic tissue inhibitor metalloproteinase (TIMP)-1 [20]. ESCs were also able to stimulate the endogenous cardiac regeneration via activating the differentiation of resident cardiac stem cells (CSCs) into cardiac myocytes [21]. Paracrine factors such as hepatocyte growth factor (HGF) and insulin growth factor (IGF)-1 have been suggested to play a significant role in this activation process [21].…”
Section: Embryonic Stem Cells (Escs)mentioning
confidence: 99%
See 2 more Smart Citations
“…These beneficial effects have been attributed to decreased collagen deposition, enhanced myocardial regeneration, and possible paracrine factors released from ESCs such as the anti-apoptotic proteins cystatin C, osteopontin, and clusterin, and the anti-fibrotic tissue inhibitor metalloproteinase (TIMP)-1 [20]. ESCs were also able to stimulate the endogenous cardiac regeneration via activating the differentiation of resident cardiac stem cells (CSCs) into cardiac myocytes [21]. Paracrine factors such as hepatocyte growth factor (HGF) and insulin growth factor (IGF)-1 have been suggested to play a significant role in this activation process [21].…”
Section: Embryonic Stem Cells (Escs)mentioning
confidence: 99%
“…Transplantation of ESCs has been shown to inhibit cardiomyocyte apoptosis and myocardial fibrosis, with subsequent improvements in adverse cardiac remodelling and cardiac function following MI [20] and in doxorubicin-induced cardiomyopathy [21]. These beneficial effects have been attributed to decreased collagen deposition, enhanced myocardial regeneration, and possible paracrine factors released from ESCs such as the anti-apoptotic proteins cystatin C, osteopontin, and clusterin, and the anti-fibrotic tissue inhibitor metalloproteinase (TIMP)-1 [20].…”
Section: Embryonic Stem Cells (Escs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, the exaggerated collagen synthesis in DIC coincides with extracellular matrix degradation consequent to activation of matrix metalloproteinases (MMPs) (17,34,36). Previous studies have demonstrated the ability of various factors and therapeutics to promote cytoprotection in acute DIC (16)(17)(18)30). However, investigation into the long-term potential of these approaches relative to chronic DIC is warranted.…”
Section: Doxorubicin (Dox)mentioning
confidence: 99%
“…Of interest, these studies admittedly acknowledged minimal to no engraftment of transplanted cells (1,37). More recently, the ability of embryonic stem (ES) cells and their released factors to repair and regenerate the injured DIC myocardium was assessed (30). Evidence provided suggested that ES cells and their conditioned media (CM) were capable of blunting acute DIC adverse conditions (30).…”
Section: Doxorubicin (Dox)mentioning
confidence: 99%